PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN PADA PT. BANK CENTRAL ASIA, TBK PERIODE TAHUN 2015-2020 - Putri Sarirati; Kristin Yunianti; Feriandy Feriandy (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
This research aims to examine the effect of Good Corporate Governance (Institutional Ownership and Board of Directors) on Profitability at PT. Bank Central Asia, Tbk for the period 2015-2020. This research uses secondary data from PT. Bank Central Asia, Tbk in 2015- 2020. The data analysis technique used is the classical assumption data and multiple linear regression test. The results of this research indicate that institutional ownership and the board of directors have no significant effect on profitability.